2021
DOI: 10.3390/catal11050555
|View full text |Cite
|
Sign up to set email alerts
|

The Catalytic Oxidation of Formaldehyde by FeOx-MnO2-CeO2 Catalyst: Effect of Iron Modification

Abstract: A series of FeOx-MnO2-CeO2 catalysts were synthesized by the surfactant-templated coprecipitation method and applied for HCHO removal. The influence of Fe/Mn/Ce molar ratio on the catalytic performance was investigated, and the FeOx-MnO2-CeO2 catalyst exhibited excellent catalytic activity, with complete HCHO conversion at low temperatures (40 °C) when the molar ratio of Fe/Mn/Ce was 2/5/5. The catalysts were characterized by N2 adsorption and desorption, XRD, H2-TPR, O2-TPD and XPS techniques to illustrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…[15] Previous works have proved that manganese oxide (MnO 2 ) possesses better low-temperature catalytic activity than other metal oxides including CuO, [12] Co 3 O 4 , [17] FeO x [18] and CeO 2 . [19] However, the narrow band gap between the electron and hole weakens the reaction activity of MnO 2 . [20] Rare earth (RE) ions exhibit various oxidation states and oxygen vacancies, which endow themselves with desirable dopants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15] Previous works have proved that manganese oxide (MnO 2 ) possesses better low-temperature catalytic activity than other metal oxides including CuO, [12] Co 3 O 4 , [17] FeO x [18] and CeO 2 . [19] However, the narrow band gap between the electron and hole weakens the reaction activity of MnO 2 . [20] Rare earth (RE) ions exhibit various oxidation states and oxygen vacancies, which endow themselves with desirable dopants.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the disadvantages of noble metal catalysts such as high costs and poor thermostabilities, [16] the development of transition metal oxides of manganese, copper, iron and cobalt becomes an alternative strategy [15] . Previous works have proved that manganese oxide (MnO 2 ) possesses better low‐temperature catalytic activity than other metal oxides including CuO, [12] Co 3 O 4 , [17] FeO x [18] and CeO 2 [19] . However, the narrow band gap between the electron and hole weakens the reaction activity of MnO 2 [20] .…”
Section: Introductionmentioning
confidence: 99%
“…Among the various methods considered, catalytic oxidation emerges as a highly promising approach due to its ability to efficiently convert HCHO into CO 2 and H 2 O at ambient conditions, while maintaining a low cost and avoiding the generation of toxic byproducts. 11 Dong et al 12 synthesized a series of metal oxide catalysts and studied the sequence of their catalytic activity at 120 °C. The findings indicated that MnO 2 demonstrated the highest conversion rate of HCHO at 80%.…”
Section: Introductionmentioning
confidence: 99%
“…Supported noble metal catalysts fulfill these requirements and are more practical materials compared with transition metal oxide catalysts which oxidize HCHO completely above ambient temperature. [5][6][7] In 2005, the Pt/TiO 2 catalyst was utilized in HCHO oxidation, oxidizing HCHO into CO 2 and H 2 O without any by-products at ambient temperature. 8 Due to the scarcity of noble metals, it is necessary to reduce the content of noble metals to reduce the cost.…”
Section: Introductionmentioning
confidence: 99%